2002
DOI: 10.3141/1796-07
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Design, Operating, and Posted Speeds on Horizontal Curves of Rural Two-Lane Highways in Nebraska

Abstract: Circular horizontal curves on rural two-lane highways in Nebraska with posted speeds of 55, 60, and 65 mph were investigated to determine the relationship of design and operating and posted speeds in an effort to provide guidelines for consistent roadway design along horizontal alignments. The mean, 85th percentile, and 95th percentile speeds; upper limit of the 16-km/h (10-mph) pace; and percent of vehicles within the pace of free-flowing passenger cars in dry, daytime conditions were analyzed at tangent appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 0 publications
0
26
0
2
Order By: Relevance
“…The 85th percentile speed is 140 km/h, 95th percentile speed is 155 km/h and 99th percentile speed is 170 km/h. Since the vehicle, speeding was indicated as the cause of the accidents, it is suggested to make the test drives by experienced drivers (Jessen et al 2001;Schurr et al 2002). So, the test drives were performed with speeds in a range from 140-170 km/h.…”
Section: Data Collectionmentioning
confidence: 99%
“…The 85th percentile speed is 140 km/h, 95th percentile speed is 155 km/h and 99th percentile speed is 170 km/h. Since the vehicle, speeding was indicated as the cause of the accidents, it is suggested to make the test drives by experienced drivers (Jessen et al 2001;Schurr et al 2002). So, the test drives were performed with speeds in a range from 140-170 km/h.…”
Section: Data Collectionmentioning
confidence: 99%
“…The average vehicle travel speed along distance traveled are be measured by GPS at every segment. Based on previous study [10], they suggested at least 300 m from the study site to any intersection or other element or stop sign that may affecting operating speeds.…”
Section: Methodsmentioning
confidence: 99%
“…Other less used speed predictors include the element extension (Krammes et al 1995;Voigt and Krammes 1996;Cardoso 1996;Schurr et al 2002), the superelevation rate (Voigt and Krammes 1996;Gibreel et al 2001;Bonneson et al 2007), and the posted speed limit (Lamm et al 1988;Schurr et al 2002).…”
Section: Literature Frameworkmentioning
confidence: 99%